2009
DOI: 10.1128/jvi.01520-08
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking through the Rev/RRE Pathway Is Essential for Efficient Inhibition of Human Immunodeficiency Virus Type 1 by an Antisense RNA Derived from the Envelope Gene

Abstract: A human immunodeficiency virus type 1 (HIV-1)-based vector expressing an antisense RNA directed against HIV-1 is currently in clinical trials. This vector has shown a remarkable ability to inhibit HIV-1 replication, in spite of the fact that therapeutic use of unmodified antisense RNAs has generally been disappointing. To further analyze the basis for this, we examined the effects of different plasmid-based HIV-1 long-terminalrepeat-driven constructs expressing antisense RNA to the same target region in HIV-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 80 publications
1
18
0
Order By: Relevance
“…In this and the previous study by Ward et al it has also been clearly demonstrated that efficient AS RNA-mediated inhibition of HIV-1 replication is Rev/RRE pathway dependent 127 . In addition, our data have demonstrated that presence of a panhandle in RRE-driven AS env RNA significantly promotes AS inhibition.…”
Section: Rre-driven Antisense Env Rna-mediated Inhibition Is Less Effmentioning
confidence: 66%
See 4 more Smart Citations
“…In this and the previous study by Ward et al it has also been clearly demonstrated that efficient AS RNA-mediated inhibition of HIV-1 replication is Rev/RRE pathway dependent 127 . In addition, our data have demonstrated that presence of a panhandle in RRE-driven AS env RNA significantly promotes AS inhibition.…”
Section: Rre-driven Antisense Env Rna-mediated Inhibition Is Less Effmentioning
confidence: 66%
“…In the construction of the HIV vectors that were used in the Ward et al study 127 ( Figure 22), a region that was complementary to part of the envelope To directly compare the inhibition that could be achieved with these vectors, constructs with and without panhandles were co-transfected into 293T cells together with the pNL4-3 proviral plasmid and inhibition was measured as a reduction in p24 levels, as previously described 127 . The result from the analysis showed that RRE-driven antisense vector with a panhandle was about 10-fold more effective in inhibiting HIV than the corresponding vector lacking a panhandle at a molar ratio of 1:1 ( Figure 25A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations